Short QT Syndrome - Bjerregaard, Preben (Ann Noninvasive Electrocardiol, 2005)
Short QT syndrome (SQTS) is an inheritable primary electrical disease of the heart, discovered in 1999. It is characterized by an abnormally short QT interval (<300 ms) and a propensity to atrial fibrillation and sudden cardiac death (SCD). Like in the case of long QT syndrome there is more than one genetic mutation that can lead to a short QT interval in the ECG and so far two have been identified. Shortening of the effective refractory period combined with increased dispersion of repolarization is the likely substrate for reentry and life threatening tachyarrhythmias. Only 22 people have been classified as having SQTS: 15 from the actual measurement of a short QT interval in their ECG and 7 by history, all having died from SCD. It is very likely that several cases, especially among children, have been overlooked, since the shortness of the QT interval only becomes apparent at heart rates <80 beats/min. The best form of treatment is still not known, but prevention of atrial fibrillation has been accomplished by propafenone, and an implantable cardioverter defibrillator is recommended for prevention of SCD.